Strong signals in HR management: How the configuration and strength of an HR system explain the variability in HR attributions - Meier‐Barthold, Madleen; Biemann, Torsten; Alfes, Kerstin (Human Resource Management, 2023)
AbstractIn explaining the effectiveness of a human resource (HR) system within an organization, scholars have turned their attention to HR attributions, which capture employees' perceptions about the intentions behind their organization's HR practices, and have demonstrated that an HR system's content and process of communication drive employees to form specific HR attributions. However, current research has not yet explained why HR attributions differ among employees. We investigate the variability in HR attributions among individuals and the organizational factors that influence this variability. Using signaling theory and the concept of situational strength, we argue that employees' HR attributions vary less when signals sent by HR management are unambiguous and the conveyed information is consistent. Using an online scenario‐based experiment with 760 participants, our findings reveal that the configuration and the strength of an HR system as well as their combination have significant effects on the variability in HR attributions among employees, and these effects differ for the different HR attributions.